2020
DOI: 10.22271/chemi.2020.v8.i5g.10340
|View full text |Cite
|
Sign up to set email alerts
|

Studies on genetic divergence (D2) for fruit yield and its related traits in pumpkin (Cucurbita moschata Duch. ex. Poir)

Abstract: The experimental material consisted of 28 pumpkin genotypes including three standard checks viz., Arka Chandan, Azad Kaddu and Pusa Vikash was conducted in a Randomized Block Design with three replications. Analysis of variance studies indicated significant differences among all the genotypes for all the characters under study. Genetic diversity was worked out using Mahalanobis D 2 statistic. Based on D 2 analysis, the genotypes were grouped into 7 distinct non-overlapping clusters. Cluster I, II and III had 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…of nodes per plant (4.97) while the low estimate was observed for the fruit equatorial circumference (9.92), node number at first staminate flower anthesis (9.03), days to first staminate flower anthesis (7.68), days to first pistillate flower anthesis (3.78) and days to first fruit harvest (3.46)" [9]. Similar findings were also marked by earlier scientist in pumpkin [12][13][14][15].…”
Section: Heritability and Genetic Advancesupporting
confidence: 72%
See 1 more Smart Citation
“…of nodes per plant (4.97) while the low estimate was observed for the fruit equatorial circumference (9.92), node number at first staminate flower anthesis (9.03), days to first staminate flower anthesis (7.68), days to first pistillate flower anthesis (3.78) and days to first fruit harvest (3.46)" [9]. Similar findings were also marked by earlier scientist in pumpkin [12][13][14][15].…”
Section: Heritability and Genetic Advancesupporting
confidence: 72%
“…"The estimates of coefficients of variation revealed that magnitude of phenotypic coefficients of variations (PCV) were higher than the genotypic coefficient, of variation (GCV) for all the characters indicating important role of environment. The phenotypic coefficient of variation ranged from 5.18 per cent (non reducing sugars) to 33.71 per cent (fruit yield per plant) for the various characters studied" [8] (Table 1).…”
Section: Phenotypic Coefficient Of Variation (Pcv)mentioning
confidence: 99%
“…A perusal of Table-3 showed that cluster means for different traits indicated considerable differences between the clusters". [7] All the clusters from cluster I to cluster VI had in general medium mean performance for most of the characters, exhibiting extreme cluster means for none of the character under the study.…”
Section: Resultsmentioning
confidence: 87%
“…The maximum inter-cluster distance was observed between clusters IV to cluster VI (1879.65), which suggested that members of these two clusters are genetically very diverse to each other. The inter cluster values between cluster I to IV (1100.17), V to VI (657.01), II to IV (1294.53), III to VI (1069.11) and IV to VI (1879.65) were very high" [7].…”
Section: Resultsmentioning
confidence: 98%
“…Analysis of contribution of the characters to genetic diversity revealed that characters like plant height (10.3%), branches per plant (0.4%), fruit weight (2.07%), yield per plant (3.4%) contributed to parameters of yield and different scientist also observed almost similar level of contribution for various growth and yield contributing characters [23,25,26,27,28,29,30,31].…”
Section: Clustersmentioning
confidence: 97%